PENGARUH PENGETAHUAN PERPAJAKAN, PEMAHAMAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, KETEGASAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WPOP - Alfia, Alfia; Rochmawati, Rochmawati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022, 2022)
Efforts to maximize tax revenue depend not only on the role of the Directorate General of Taxes and tax officials, but also on the role of taxpayers themselves. Individual taxpayer compliance is influenced by several aspects including tax knowledge, taxpayer understanding, taxpayer awareness and the firmness of tax sanctions. This study was conducted to analyze the effect of tax knowledge, taxpayer understanding, taxpayer awareness and the firmness of tax sanctions on WPOP compliance. The population in this study were all individual taxpayers registered at KPP Pratama Surabaya Mulyorejo with a sample size of 100 taxpayers based on the slovin formula. This type of research is quantitative using a questionnaire. The data analysis technique in this study used multiple linear regression analysis. The results of this study simultaneously show that all independent variables have an effect on individual taxpayer compliance. Taxation knowledge and taxpayer awareness partially affect taxpayer compliance, but taxpayer understanding and firmness of tax sanctions do not affect individual taxpayer compliance